Thermal properties of tile and marble - Noor Zaniza Wati, Zainol (Universiti Malaysia Sarawak, UNIMAS, 2005)
The research of thermal properties in materials science is important because we can exploit the features or characteristics of that material as purpose to enhance human life. Therefore, heat transfer plays an utmost role in application of tile and marble such as floor, wall or any decoration. It can be determined through an experiment of heat lost and heat gain of that materials.